The Anti‐Müllerian Hormone Profile is Linked with the In Vitro Embryo Production Capacity and Embryo Viability after Transfer but Cannot Predict Pregnancy Outcome. Issue 2 (4th March 2016) - Ghanem, N; Jin, JI; Kim, SS; Choi, BH; Lee, KL; Ha, AN; Song, SH; Kong, IK
Contents: The current study investigated the possibility of using the AMH concentration as a predictor of the ability of Korean Hanwoo cows to produce cumulus‐oocyte complexes, embryos that survive after transfer as well as the pregnancy outcome of surrogates. Eight sessions of ovum pick‐up (OPU) were performed with 19 donor cows at an interval of 3–4 days. Antral follicle count (AFC), oocyte quality and in vitro embryo development were recorded for each cow. Embryos produced from cows with different AMH profiles were transferred into recipients (n = 96). Cows in the high (≥0.25 ng/ml) and intermediate (0.1≥ to <0.25 ng/ml) AMH groups had a significantly higher AFC per OPU session (20.40 ± 1.36 and 16.91 ± 1.52, respectively; mean ± standard deviation) than cows in the low AMH group (<0.1 ng/ml; 12.19 ± 2.14). In addition, more cumulus‐oocyte complexes per donor were recovered in the high (11.46 ± 1.22) and intermediate (7.38 ± 0.83) AMH groups than in the low AMH group (4.77 ± 0.44). The percentage of oocytes reached blastocyst stage was significantly higher in the intermediate (47.0%) and high (38.5%) AMH groups than in the low AMH group (32.3%). The number of embryos produced per cow was higher in the high (3.9 ± 0.2) and intermediate (6.9 ± 0.6) AMH groups than in the low AMH group (2.2 ± 0.3). The percentage of embryos that gave birth to viable calves when transferred into recipients was higher for those derived from cows in the intermediate AMH group (50.7%) than for those derived from cows in the low (35.7%) and high (36.4%) AMH groups. In conclusion, a single measurement of AMH concentration predicted the in vitro embryo production potential of donor Korean native cows before OPU and is linked with embryo viability after transfer into recipients.